Analisis Faktor Risiko Gout Arthritis - Irmawati RJ; Elsi Tandi Pailan; Baharuddin Baharuddin (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
Gout arthritis is an inflammatory disease in the joints, which is still very high and is still a public health problem, especially in Indonesia with a high prevalence. This study aims to determine the risk factors that influence the incidence of Gout arthritis. Quantitative research with a case control study approach. A sample of 60 respondents was 30 each for the case and control groups. The instrument used in this study was in the form of a questionnaire or questionnaire. The data were analyzed using the chi-square test. Genetic statistical test results with values p = 0.002 (<0.05) OR = 6.909 (95% Cl 2.160-22.098), while uric acid levels and purine consumption with p values = 0.558 (>0.05), OR = 1.556 (95% Cl 0.534-4.532) and p = 0.055 (>0.05), OR = 3,500 (95% Cl 1,112-11,017). The conclusion that genetics have a significant influence, while uric acid levels and foods containing purines have no influence on Gout arthritis